Educational design research: grappling with methodological fit - Jacobsen, Michele; McKenney, Susan (Educational technology research and development, 2024)
Educational Design Research (EDR) employs a diverse range of methods to study learning, teaching, design, and technology—and new ones are shared in this special issue. We contend that a focus on methods inherently requires examination of the questions they are used to answer and the ways in which the resulting findings advance scientific understanding. Specifically, this article focuses on obtaining and guarding methodological fit in EDR. It describes three main orientations to research inherent in EDR trajectories (research for, on, and through interventions), the kinds of questions we ask in each, how our methods evolve accordingly, and challenges to alignment that are often encountered along the way. Thereafter, it offers examples of the three orientations in two different doctoral studies on innovative educational technologies, each of which demonstrates methodological fit as well as relevance for practice despite the phase-related shifts in focus, questions, and methods. The article concludes with a framework for assessing methodological fit both within and across the three orientations to EDR in two studies, along with broader recommendations for conducting EDR in the field of educational technology.